Assessment of the State of Competition in Ukraine by the Results of a Survey of Domestic Enterprises - M. POTAPOVA; V. TALAKH; L. OPANASENKO (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Formation and implementation of the state competition policy requires a clear understanding of the current state of the competitive environment, and the effectiveness of previous measures taken by the government.The article studies the state of the competitive environment in Ukraine based on the results of a survey of business executives, conducted annually by the Centre of Complex Research in Antimonopoly Policy. Responses of the executives allow assessing the degree of competition in the business environment. The survey finds that in Ukraine domestic competition is more important than competition from foreign companies.Although significant and moderate competition from domestic and foreign firms was felt by 73.5% and 35.3% of respondents, respectively, only 25.6% and 15.1% noted that competition resulted in lower prices and costs. Therefore, nowadays the most acute problem is not so much the presence of competition in domestic markets, but the effectiveness of competition policy.The survey conducted a research of respondents' assessment of the level of dominance in the region using the method of the World Economic Forum.A quarter of respondents said in 2019 that competition policy in their region was partially effective and stimulated competition in individual market segments.The results of the study showed an improvement in the enterprises' evaluation of the effectiveness of the state competition policy, which includes, first of all, the activities of the Antimonopoly Committee of Ukraine.The analysis can be used in the development of competition policy documents.